Journey into Amazonia - National Geographic Channel; PBS Online (Alexandria, Va. : PBS Online, 2011)
Companion to the PBS series which attempts to capture the spirit of the world's largest tropical wilderness, the Amazon Basin rainforest offering a closer look at rarely seen animals as they contend with the volatile waters of the world's largest river system. Also includes essays on useful plants of the Amazon and on the status of conservation of the Amazon basin.
Keywords: Amazon River Region; Natural history -- Amazon River Region; Nature -- Effect of human beings on -- Amazon River Region